Optimization of Rotary Blade Wear and Tillage Resistance Based on DEM-MBD Coupling Model - Zhiqiang Mao; Yang Zhang; Keping Zhang; Jiuxin Wang; Junqian Yang; Xiaobao Zheng; Shuaikang Chen; Zhongqing Yang; Biao Luo (Agriculture)
To solve the problems of high tillage resistance and the rapid wear of the rotary blade during tillage, this study employed a coupled algorithm of the discrete element method (DEM) and multi-body dynamics (MBD) with Hertz–Mindlin with JKR particle contact theory to establish a rotary blade–sandy soil model. The interaction between the rotary blade and sandy soil was analyzed. The results indicated that the lateral and horizontal resistances of the rotary blade reached the peak values near the maximum tilling depth, whereas the vertical resistance reached its peak earlier. Blade wear predominantly occurred on the side cutting edge, bending zone edge, and sidelong edge, with the most significant wear observed on the sidelong edge, followed by the bending zone edge and side cutting edge, which showed similar wear patterns. To reduce wear and tillage resistance, Box–Behnken optimization was applied to optimize the blade’s local parameters. The optimal parameters—the height of the tangent edge end face was 51 mm, the bending radius was 28 mm, and the bending angle was 116°—reduced wear by 22.4% and tillage resistance by 12%. A soil disturbance analysis demonstrated that the optimized blade performs better in terms of tillage width compared to the unoptimized blade. The optimized rotary blade achieves the effects of reduced resistance and wear, improves the lifespan of the blade, reducing material loss, and meeting the requirements of sustainable agricultural production.